The prevalence of insufficient iodine intake in pregnancy in Africa: a systematic review and meta‑analysis - Bitamazire Businge, Charles; Tafadzwa Musarurwa, Hannibal; Longo‑Mbenza, Benjamin; Kengne, Andre Pascal (Systematic Reviews, 2019)
Fortification of foodstuffs with iodine, mainly through iodization of salt, which commenced in several African countries after 1995 is the main method for mitigating iodine deficiency in Africa. We assessed the degree of iodine nutrition in pregnancy across Africa before and after the implementation of national iodine fortification programs (CRD42018099434). Methods: Electronic databases and gray literature were searched for baseline data before implementation of population- based iodine supplementation and for follow-up data up to September 2020. R-metamedian and metamean packages were used to pool country-specific median urinary iodine concentration (UIC) estimates and derived mean UIC from studies with similar features. Results: Of 54 African countries, 23 had data on iodine nutrition in pregnancy mostly from subnational samples. Data before 1995 showed that severe iodine deficiency was prevalent in pregnancy with a pooled pregnancy median UIC of 28.6 μg/L (95% CI 7.6–49.5). By 2005, five studies revealed a trend towards improvement in iodine nutrition state in pregnancy with a pooled pregnancy median UIC of 174.1 μg/L (95% CI 90.4–257.7). Between 2005 and 2020 increased numbers of national and subnational studies revealed that few African countries had sufficient, while most had mildly inadequate, and some severely inadequate iodine nutrition in pregnancy. The pooled pregnancy median UIC was 145 μg/L (95% CI 126–172). Conclusion: Improvement in iodine nutrition status in pregnancy following the introduction of fortification of foodstuffs with iodine in Africa is sub-optimal, exposing a large proportion of pregnant women to the risk of iodine deficiency and associated disorders.
Keywords: Iodine; Insufficiency; Pregnancy